Rola doświadczenia w artystycznym kształceniu akademickim na przykładzie założeń dydaktyczno-artystycznych Pracowni Komunikacji Twórczej prowadzonej w Akademii Sztuk Pięknych im. Eugeniusza Gepperta we Wrocławiu = The role of experience in artistic academic education on the example of didactic and artistic assumptions of Creative Communication Studio run at The Eugeniusz Geppert Academy of Art and Design in Wroclaw - Józefowski, Eugeniusz (1956- ); Florczykiewicz, Janina (Kraków ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
The authors of the article present the Creative Communication Studio against the backdrop of changes in artistic education. They present the didactic concept of running the studio and the functions it fulfills in the course of education in the field of art mediation. They present sample tasks. The essence of this concept of education is to create didactic situations that initiate the process of acquiring knowledge about art by directly experiencing it.
Keywords: kształcenie artystyczne; akademia sztuk pięknych; Pracownia Komunikacji Twórczej; artistic education; academy of fine arts; Creative Communication Studio